Design and Development a Web Platform Portal for Mosque Financial Management - Sukya, Fadelis; Nurfarida, Ellya (LPPM Telkom University Surabaya, 2024)
Transparency and accountability in the financial management of mosques is an area that requires significant attention because it builds the initial trust of the mosque in collecting funds through infaq and waqf. Currently, many mosques still use whiteboards as a tool to present their financial reports. This poses a problem for mosques when delivering financial reports to donors who live far away. Therefore, a tool that can serve as a medium for financial reporting is needed. Based on this need, the research aims to create a web-based mosque financial portal to record income (donations, alms), qurban records, and expenses. In other applications, each mosque uses an application designed for each mosque. This software has been developed to accommodate the needs of each mosque and is integrated into a single application portal. The development of this application uses the Waterfall method, which involves various stages such as user requirements, system design, implementation, and testing. This financial portal was successfully implemented in 11 mosques and prayer rooms across 5 provinces. This application features recording income (donations and alms), qurban records, and expenditure records. The test results show that many mosques can use this financial management portal to record income and expenses. Finally, we can conclude that this web-based mosque financial portal would be a viable solution to enhance the accountability services of mosques in managing their finances.